2012
DOI: 10.1039/c2an35397k
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling of Curcuma species grown in different regions using 1H NMR spectroscopy and multivariate analysis

Abstract: Curcuma is used to treat skin diseases and colic inflammatory disorders, and in insect repellants and antimicrobial and antidiabetic medications. Two Curcuma species (C. aromatica and C. longa) grown in Jeju-do and Jin-do were used in this study. Methanolic extracts were analyzed by (1)H NMR spectroscopy, and metabolite profiling coupled with multivariate analysis was applied to characterize the differences between species or origin. PCA analysis showed significantly greater differences between species than or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
1
25
1
Order By: Relevance
“…Curcuma can contain up to a few dozen micromolar concentrations of betaine 50 , which is insignificant compared to the levels of betaine found in this study, and can thus be neglected. The metabolism of betaine in the rat liver as a catabolic product of choline in and out of the mitochondria is represented in Fig.…”
Section: Discussioncontrasting
confidence: 70%
“…Curcuma can contain up to a few dozen micromolar concentrations of betaine 50 , which is insignificant compared to the levels of betaine found in this study, and can thus be neglected. The metabolism of betaine in the rat liver as a catabolic product of choline in and out of the mitochondria is represented in Fig.…”
Section: Discussioncontrasting
confidence: 70%
“…Earlier researches also revealed that the concentrations of reducing sugars ( e . g ., glucose and fructose) and organic compounds in plant are related to temperature, low temperature will induce reducing sugars and organic compounds accumulation 39, 40 . However, this result was not completely repeated in the present study, such as malic acid level were higher in H .…”
Section: Discussionmentioning
confidence: 99%
“…NMR has several advantages over other methods (LC/MS, GC/MS), including simple sample preparation, high reproducibility, non-selective, non-destructive and the capacity to elucidate structures [14]. Non-targeted metabolomic profiling based on 1 H NMR spectroscopy has been successfully applied to discriminate species or different origins of Curcuma [15], Radix Bupleuri [16], Danggui [17], and quality control of Polygonum [18], Pueraria [19], Angelica acutiloba roots [20] and Magnoliae officinalis cortex [21].…”
Section: Introductionmentioning
confidence: 99%